[De]Politicizing the Pandemic: Visually Communicating Digital Public Sociology. - Robinson, Laura; Trammel, Juliana M.; Moles, Katia (American Behavioral Scientist, 2025)
In the context of the COVID-19 infodemic, we explore discourse around a highly polarized health issue: mask wearing during the pandemic. Probing ideologically charged discourse from #masks on Twitter, we examine the potential for visual tools to promote digital citizen social science. Our case study reveals the promise of visualization to make ideological discourse on social media more easily identifiable by members of the general public. This leads us to argue that accessible visualization tools are needed for the public to ethically engage as digital citizen social scientists who actively analyze their own media consumption and outputs. Doing so would potentially awaken the sociological imagination by giving digital prosumers the agency to contextualize the social structure of debate around issues of public concern. In this way, visualizations of social media may ignite the sociological imagination in the tradition of digital public sociology.